IDENTITY PROBLEMS IN TURKEY: ALEVIS and AKP - (:unkn) unknown (INT ORGANIZATION CENTER ACAD RESEARCH, 2015)
As successive Turkish governments have attempted, AKP too is trying to solve the perennial Alevi problem as part of its broader agenda regarding the question of minorities. However, this paper argues that there are two fundamental obstacles facing Turkey's conservatives in reaching a meaningful solution. First, there is the ontological issue that AKP itself does not represent a radical break with the country's tumultuous past in terms of perception toward Alevis. Secondly, there is the ideological issue that the Sunni majority, who are at the core of AKP's concept of oppressed Muslims, are hardly sympathetic to Alevi rituals or complaints. Decades long effects of Turkish-Islamic synthesis did not bode well for that effort also. So, any recognition of equal status on religious grounds for Alevis would create a backlash for the ruling party among its rural electorate.
Keywords: AKP; Alevis; Turkey; Religion; Secularism